Trends and new developments in employment services to support transitions in Sub-Saharan Africa, the Middle East and North Africa regions - Eamonn Davern (International Labour Organization (ILO), 2020)
This paper presents the findings of a survey undertaken in selected countries in the Sub Saharan Africa and Middle East and North Africa regions (SSA and MENA) aimed at reviewing the status of employment service provision, challenges and opportunities for their development 4207 Given the enormous employment challenges in the Sub Saharan Africa and Middle East and North Africa regions, particularly for youth and vulnerable groups, the study confirms the potential role employment services can play, including improving the quality of employment in the formal economy as well as promoting the formalization of the informal jobs and enterprises. While public employment services (PES) are at different levels in different countries, they share the weakness in capacity. In order to address these challenges, governments need to invest in resourcing the PES and setting up a clear and conducive legal and policy framework. The institutional framework for PES seem to play a critical role - PES organized as executive agencies tended to be stronger, more effective and efficient than those that were part of the Ministries of Labour with some exceptions. The paper recommends that PES adopt digital technology in service delivery with a balanced offer of physical services to ensure inclusion, explore the use of partnerships with other public organizations, private employment agencies and third sector service providers, and focus on employer services where labour demand is low while adopting a more realistic phased approach to service development. The study was undertaken as part of the ILO/GIZ Youmatch Programme collaboration
Keywords: 330; future of work; employment; informal employment; temporary employment; youth employment; employment policy; employment creation; employment services; youth unemployment; skills; youth